2019
DOI: 10.5812/ijcm.82413
|View full text |Cite
|
Sign up to set email alerts
|

Endocan Expression Profile in Different Grades of Oral Squamous Cell Carcinoma

Abstract: Background: Oral cancer is one of the most prevalent malignancies and presents increasing incidence and mortality trends in the world, with a mortality rate of 14.33%. Oral squamous cell carcinoma (OSCC) constitutes 90% of all malignancies in the oral cavity. In spite of new therapeutic strategies, the risk of metastasis and mortality rate is still very high. Methods: A total of 54 samples (18 samples of each grade) were collected from the archives of the Pathology Department of Be'sat Educational Hospital, Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Several studies have found a significant association between endocan-MVD and tumor grade in various neoplasms. A study on 58 cases of oral squamous cell carcinoma found that a higher endocan-MVD count was seen in an intermediate and high grade of oral squamous cell carcinoma as compared to the low-grade tumor (Irani and Amiri, 2019). A study on gastric cancer also discovered a significant association of high endocan-MVD with poorly differentiated carcinomas (Chang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found a significant association between endocan-MVD and tumor grade in various neoplasms. A study on 58 cases of oral squamous cell carcinoma found that a higher endocan-MVD count was seen in an intermediate and high grade of oral squamous cell carcinoma as compared to the low-grade tumor (Irani and Amiri, 2019). A study on gastric cancer also discovered a significant association of high endocan-MVD with poorly differentiated carcinomas (Chang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…CADM1 , a cell adhesion molecule is altered in HNSCC due to promoter hypermethylation and correlates with the poor overall survival (OS) of the patients 54 . BRCA1 / 2 , the key tumor suppressor genes exhibit varying degrees of expression in different grades of OSCC 55 56 …”
Section: Introductionmentioning
confidence: 99%